Respuesta :
The factorization of given expression is:
[tex]216x^{12}-64 = 8\left(3x^4-2\right)\left(9x^8+6x^4+4\right)[/tex]
Solution:
Given that we have to factorize the given expression
Given expression is:
[tex]216x^{12}-64[/tex]
Let us factorize the expression
[tex]\text{ Rewrite } 64 \text{ as } 8 \times 8[/tex]
[tex]\text{Rewrite } 216 \text{ as } 8 \times 27[/tex]
Thus the given expression becomes,
[tex]216x^{12} - 64 = (8 \times 27)(x^{12}) - (8 \times 8)\\\\\text{Factor out common term 8 }[/tex]
[tex]216x^{12} -64= 8(27x^{12}-8)[/tex]
[tex]\mathrm{Rewrite\:}27x^{12}-8\mathrm{\:as\:}\left(3x^4\right)^3-2^3[/tex]
[tex]8(27x^{12}-8) = 8(\left(3x^4\right)^3-2^3)[/tex]
Let us apply the difference of cubes formula
[tex]x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right)[/tex]
[tex]\left(3x^4\right)^3-2^3=\left(3x^4-2\right)\left(3^2x^8+2\cdot \:3x^4+2^2\right)[/tex]
Therefore,
[tex]8(27x^{12}-8) = 8\left(3x^4-2\right)\left(3^2x^8+2\cdot \:3x^4+2^2\right)\\\\8(27x^{12}-8) = 8\left(3x^4-2\right)\left(9x^8+6x^4+4\right)[/tex]
Thus factorization of given expression is:
[tex]216x^{12}-64 = 8\left(3x^4-2\right)\left(9x^8+6x^4+4\right)[/tex]